"Independenter a civili potestate" (c. 1254 § 1 CIC): zur Legitimität staatlich sanktionierter Kirchenfinanzierungssysteme - Pree, Helmuth (Zeitschrift für katholische Theologie, 1996)
"The Catholic Church" insists on "the inherent right, independently of any secular power, to acquire, retain, administer and alienate temporal goods, in pursuit of its proper objectives" (c 1254 § 1). The following considerations are dealing with models of financial organization of the Catholic Church where it is cooperating with the state and even using the state's help to succeed with dilatory paying faithful. After introducing the models of Germany, Austria and Italy the author discusses the legitimation of these models. Besides fundamental considerations the criterions for a legitimate ecclesial financial organization are elaborated. The author compares the above mentioned models with these criterions and points out the advantages and disadvantages of the different models.